Pengaruh Lingkungan Keluarga terhadap Pilihan Karir Siswa - Siti Marti'ah; Berta Dian Theodora; Haryanto Haryanto (Universitas Indraprasta PGRI Jakarta, 2018)
Students often have problems when choosing a career. This will hinder students from achieving an optimal career selection. Senior High School (SMA) students often carry outcareer exploration and decision-making with indecision, uncertainty and stress. The research is conducted at State Senior High School (SMAN) in Depok. The population of the study is students of class XII, with 358 sample of students randomly selected from 12 schools. The research uses a quantitative approach with one way anova. Data are collected through literature review and questionnaire. Hypothesis of research to be tested is there are significant differences of career readiness between students with a supportive family environment and those with a less-supportive family environment. The result of anova calculation has a sig value of 0.000 <0.05, so it can be interpreted that there are differences in the readiness of career selection between students with a supportive family environment and those with a less-supportive family environment.